99mTc-Aminohexylidendiphosphonate and 99mTc-Pyrophos phate in the Scintigraphic Diagnosis of Experimental Cardiomyopathy in Dogs - Duška, F.; Hadaš, L.; VižĎa, J.; Kafka, P.; Mazurová, Y.; Palicka, V.; Grossman, V. (Nuklearmedizin - NuclearMedicine, 1987)
Experimental cardiomyopathy was provoked in 24 dogs with high intravenous doses of adrenaline and theophylline. These lesions were studied by means of the new agent 99mTc-AHDP and 99mTc-PYP in comparison. Cardiomyopathy could be imaged as early as 4 h after the onset of involvement but not later than 7 days. A maximum accumulation occurred in lesions 24 h old. 99mTc uptake in the myocardium was graded scintigraphically. 99mTc-AHDP was accumulated in the altered’myocardium to a greater extent than 99mTc-PYP. Scintigraphic findings were in good agreement with plasma levels of creatine- kinase. A comparison with histology demonstrated that the maximum accumulation of radiopharmaceuticals occurred at the time when the development of myocardium involvement reached the stage of myocytolysis.